A circularly polarized pyramidal horn antenna based on substrate integrated waveguide. Issue 12 (4th November 2022) - Du, Heng; Wang, Weihua
Abstract: A circularly polarized pyramidal horn antenna based on substrate integrated waveguide (SIW) technology is proposed and developed for Ku‐band applications. The proposed horn antenna is excited by the upper and lower SICL differential feed networks placed vertically to each other, so that two orthogonal waveguide modes with the equal amplitude are generated at the horn aperture. A 90° coupling network based on SICL technology is proposed to achieve a 90° phase difference between the two orthogonal waveguide modes, thus realizing the function of left‐hand circular polarization (LHCP) and right‐hand circular polarization (RHCP) of the horn antenna. In addition, in order to make the phase distribution of the horn aperture more uniform, a cross metal strip structure at the horn aperture is proposed, thereby improving the radiation efficiency. The proposed horn antenna is manufactured by using low‐cost printed circuit boards (PCBs) process. The measured results show that the proposed circularly polarized pyramidal horn operates at center frequency 12.5 GHz, the measured gain is 8.4 dBi, the relative standing wave and axial ratio (AR) bandwidth are approximately 24% and 5%, respectively. And the radiation aperture efficiency is as high as 78.5%. The developed circularly polarized pyramidal horn antenna can be applied in the field of satellite communications.